Complex Decisions between Care and Paid Work A Qualitative Study on the Demand for Childcare Services in Mexico City - Muller, Miriam (World Bank E-Library Archive, 2020)
This study aims to improve the understanding of the barriers and enabling factors determining the demand for childcare in Mexico City. The study is based on focus group discussions and individual in-depth interviews with mothers and fathers (married or living in a union) of children ages zero to six years. The findings of this qualitative analysis confirm that for parents in Mexico City, decisions in favor of or against the use of childcare are based on: (1) the interplay between women's aspirations, the role of work in their lives, and the additional support they have; and (2) their perceptions of the care available, including convenience, overall quality, perceived opportunities for positive child development, and financial and non-financial costs (safety and risks to the child's well-being). The findings suggest that significant differences exist between women with higher education and those with lower levels of education living in different parts of the city (and from different socioeconomic backgrounds: middle-class vis-a-vis vulnerable women). The observed gaps are due to differences in their ability to make informed choices, their aspirations and work opportunities, the alternative support options available to them, and their ability to adapt to the childcare supply. These results highlight the relevance of: (1) promoting a more balanced distribution of childcare responsibilities between men and women; (2) communicating more transparently the benefits of using childcare services and the measures taken to ensure the safety and positive development of children; and (3) adapting the childcare centers' functioning to the needs of working parents